Improving Students’ Writing Ability Using Digital Multimodal Composition at SMAN 1 Katibung - Erlangga Rohmat Nafan; Mutiara Ayu (International Journal of Research in Education, 2025)
This research aims to enhance the descriptive writing abilities of tenth-grade pupils at SMAN 1 Katibung through Digital Multimodal Composition. The study showed that tenth-grade students faced difficulties in writing due to issues such as a limited vocabulary, grammatical structures, and expressing their ideas effectively. The research design is Classroom Action Research (CAR) following the approach of Kemmis and McTaggart, which includes 4 stages: planning, action, observation, and reflection. The research was completed over two cycles, with each cycle comprised of two meetings. The researcher utilized a writing test, observations, interviews, and document reviews as part of the methodology. The researcher using slide presentations and videos as digital media. The results demonstrated that the average score of pupils in the post-test of cycle 1 increased to 67% from 57% after the implementation of Digital Multimodal Composing media. Due to the percentage still falling short of the criteria, the researcher adjusted the plan for cycle 2, demonstrating enhancements in content, vocabulary, organization, grammatical structure, and mechanics. The difference approach taken in cycle 2 proved effective, resulting in 77% of students achieving the minimum standard score (KKM), which met the success criteria. According to the data assessment, the researcher found that the use of Digital Multimodal Composing media received positive feedback from students and enhanced their writing skills.